Measuring Parental Presence in the Neonatal Intensive Care Unit - Powers, Shelby A.; Taylor, Katherine; Tumin, Dmitry; Kohler, John A., Sr. (American Journal of Perinatology, 2020)
Parental presence is believed to improve outcomes for infants hospitalized in the neonatal intensive care unit (NICU). As a result, NICU policies and procedures have evolved to support parental presence, and a growing number of studies examine the role of parental presence in the NICU. However, the measurement of parental presence is not standardized, complicating assessment of its impact on child and parent outcomes across studies. We reviewed 29 studies that presented 27 distinct methods of quantifying parental presence in the NICU and reported associations of presence with patient demographics, parental engagement in the NICU, and outcomes for both infants and parents. This overview provides a foundation for standardizing and improving routine measurement of parental presence in the NICU.Key Points
Keywords: neonatal intensive care; father; mother; parental presence; parental engagement; family centered care